The Grey Line Modern Corporate Espionage and Counter Intelligence - Brown, Andrew (Amur Strategic Research Group, 2022)
Corporate espionage is an inescapable reality of the modern global business world. The Grey Line is the comprehensive examination of how modern day private sector spies operate, who they target, how they penetrate secure systems and subvert vulnerable employees. Additionally, the book provides invaluable resources for companies and individuals to use in deterring and defeating corporate spies.